Pseudomonas pseudoalcaligenes KF707 grown with biphenyl expresses a cytochrome caa(3) oxidase that uses cytochrome c(4) as electron donor - Sandri, Federica (FEBS Lett, 2018)
Combining peroxidase activity based haem-staining (TMBZ/SDS-PAGE) with mass spectrometry analyses (Nano LC-MS/MS) of protein extracts from wild type and appropriate mutants, we provide evidence that the polychlorinated biphenyl (PCB) degrader Pseudomonas pseudoalcaligenes KF707 primarily expresses a caa(3)-type cytochrome c oxidase (caa(3)-Cox) using cytochrome (cyt) c(4) as an electron donor in cells grown with biphenyl versus glucose as the sole carbon source. Homology modeling of KF707 caa(3)-Cox using the three-dimensional structure of that from Thermus thermophiles highlights multiple similarities and differences between the proton channels in subunit I of the aa(3)- and caa(3)-Cox of Paracoccus and Thermus spp., respectively. To our knowledge, this is the first report demonstrating the presence of a caa(3)-Cox using cyt c(4) as an electron donor in a Pseudomonas species.